MINFLUX nanoscopy enhanced with high-order vortex beams - Xiao-Jie Tan; Zhiwei Huang (Light: Science & Applications)
Abstract Minimal photon fluxes (MINFLUX) nanoscopy has emerged as a transformative advancement in superresolution imaging, enabling unprecedented nanoscale observations across diverse biological scenarios. In this work, we propose, for the first time, that employing high-order vortex beams can significantly enhance the performance of MINFLUX, surpassing the limitations of the conventional MINFLUX using the first-order vortex beam. Our theoretical analysis indicates that, for standard MINFLUX, high-order vortex beams can improve the maximum localization precision by a factor corresponding to their order, which can approach a sub-nanometer scale under optimal conditions, and for raster scan MINFLUX, high-order vortex beams allow for a wider field of view while maintaining enhanced precision. These findings underscore the potential of high-order vortex beams to elevate the performance of MINFLUX, paving the way towards ultra-high resolution imaging for a broad range of applications.